2013
DOI: 10.1094/php-2013-1125-01-rv
|View full text |Cite
|
Sign up to set email alerts
|

Host Defenses Associated with Fruit Infection by Colletotrichum Species with an Emphasis on Anthracnose of Blueberries

Abstract: Defense mechanisms in fruit against invasion by fungal pathogens fall into several categories, including fruit physiological factors, passive defense responses, and active defense responses. Colletotrichum spp. are common fruit rot pathogens on a variety of crops. The infection strategy of Colletotrichum pp. varies depending upon the host and the tissue type being colonized and range from hemibiotrophy to necrotrophy. Anthracnose fruit rot caused by C. acutatum is the most important postharvest disease of blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…to anthracnose 46 . Previous studies have also shown that fruit rot pathogens, Colletotrichum spp., can successfully infect blueberry fruit after only 10 to 12 h postinoculation 26,47 and induce chemical changes in fruit as early as 24 h after incubation 27 . Moreover, in preliminary studies, we showed that field-collected anthracnose-infected fruit had levels of spore concentrations similar to those used in our experiment (1.0 × 10 7 per mL).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…to anthracnose 46 . Previous studies have also shown that fruit rot pathogens, Colletotrichum spp., can successfully infect blueberry fruit after only 10 to 12 h postinoculation 26,47 and induce chemical changes in fruit as early as 24 h after incubation 27 . Moreover, in preliminary studies, we showed that field-collected anthracnose-infected fruit had levels of spore concentrations similar to those used in our experiment (1.0 × 10 7 per mL).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to remove the conidia from any extracellular enzymatic compounds, a 'filtered' solution was prepared by sterile filtering (Cameo 25 GAS, 0.22 µm; Osmonics Penang, Malaysia) the 'colony' spore suspension described above immediately before use (following methods by Waller et al 19 ). Treated fruit were left to incubate at room temperature for 48 h before use in choice and no-choice assays (see below) to allow the solutions to settle on the fruit surface; this anthracnose incubation period is sufficient to activate defensive genes and induce secondary metabolite production in blueberries 27 . A group of 5 fruit from each treatment was set aside to confirm C. fioriniae infection by checking for symptoms (only fruit treated with the C. fioriniae 'fruit' and 'colony' solutions were symptomatic).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A particularly cell wall is a notable factor for strawberry resistance or susceptibility (Amil- Ruiz et al 2011). During fruit ripening, some physiological changes occur including cell wall expansion, fruit softening, changes in pH and increase in soluble sugars and the susceptibility of fruits to pests and diseases increase (Miles and Schilder 2013). The plant's ability to synthesize a broad range of secondary metabolites (flavonoids, flavanols, triterpenes, phenolics) is pre-form biochemical barriers and to protect strawberry and raspberry from fungal pathogens and pests (Terry et al 2004;Hukkanen et al 2007;Hanhineva et al 2009;Lee 2010;Slatnar et al 2016).…”
Section: Structural and Mechanical Protection Against Fungal And Bacterial Pathogensmentioning
confidence: 99%